The Relationship between Principal Leadership and Teacher Performance with Student Characteristics Based on Local Culture in Senior High Schools - Nurdin Kaso; Nurul Aswar; Firman Firman; Dodi Ilham (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
This study aims to determine: the relationship between principal leadership and teacher performance, the relationship between principal leadership and student character based on local culture, the relationship between teacher performance and student character based on local culture, and the relationship between principal leadership and student character based on local culture through teacher performance. This research is a quantitative study with a correlational design. The research approach is managerial, pedagogical, sociological, and psychological approaches. The data collection instruments used were questionnaires, observation guidelines, interviews, and documentation. Analysis of research data using editing, coding, and tabulating. The results of the data analysis show that there is a significant influence of principal leadership with teacher performance, principal leadership with student character based on local culture, teacher performance with student character, and principal leadership with student character based on local culture through teacher performance with a significance value of 0.000 < 0.05, which means that Ha is accepted and Ho is rejected. The results of these data are significant: there is a significant relationship between the principal's leadership variable and teacher performance; there is a significant relationship between the principal's leadership variable and student character; There is a significant relationship between teacher performance variables and student character; there is a relationship between the principal's leadership variable and student character through teacher performance.